Applying Systemic Accident Model to Learn from Near-Miss Incidents of Train Maneuvering and Operation. Issue 19 (2016) - Fukuda, Keisuke; Sawaragi, Tetsuo; Horiguchi, Yukio; Nakanishi, Hiroaki
Abstract: This study proposes a novel method for safety management in train operation and maneuvering based upon Hollnagel's functional resonance analysis method (FRAM), which assumes that components of a system interact mutually and resonantly. According to the original FRAM, the general functions of train drivers' and conductors' tasks are defined, and the normal procedure of a common case is represented. Our method first attempts to replay how fluctuations of some of the tasks propagate through the entire system. Then we examine whether a countermeasure found by replaying is valid under various situations. In this way, we demonstrate that our method is able to detect latent hazards of the system as well as to identify how the system is influenced by various external and internal changes.